Optimization and mathematical modeling of communication networks - Bezruk, V. M.; Семенець, В. В.; Chebotarova, D. V.; Kaliuzhniy, N. M.; Guo Qiang; Zheng Yu (PC «Technology Center», 2019)
The main attention is paid to optimization issues, as well as mathematical modeling of systems that are important for the initial stages of the design of communication networks. Examples of solving scalar and vector optimization problems are given taking into account mathematical models of various types of communication networks. Information is given about standard sofware packages that can be used for optimization and computer simulation of communication networks.
Keywords: communication networks; mathematical modeling of systems; Numerical methods of scalar optimization